A Novel Chiral Metasurface with Controllable Circular Dichroism Induced by Coupling Localized and Propagating Modes. Issue 6 (15th March 2016) - Wang, Zeng; Wang, Yue; Adamo, Giorgio; Teh, Bing Hong; Wu, Qing Yang Steve; Teng, Jinghua; Sun, Handong
Abstract : A novel chiral metasurface composed of a chiral arrangement of nanoslits is developed. Controllable and remarkably strong chiral responses are achieved by taking advantage of the coupling between localized and propagating surface plasmon modes. The finding provides an extra degree of freedom in manipulating chiral responses.